SPIRAL CIVIC RESEARCH LEARNING MODEL (SCRLM): PENDEKATAN FLIPPED CLASSROOM–COGNITIVE APPRENTICESHIP DALAM PROJECT-BASED LEARNING UNTUK MENINGKATKAN KETEPATAN WAKTU PROYEK DAN CIVIC DISPOSITION PADA MATAKULIAH KEWARGANEGARAAN (EDUTECH, 2026)
This developmental research aims to produce a valid and effective Spiral Civic Research Learning Model (SCRLM) a Flipped Classroom model based on Cognitive Apprenticeship within Project-Based Learning with a five-cycle spiral approach—to improve project timeliness and civic disposition of students in Civics Education courses. Using Research and Development approach with the ADDIE model integrated with Bruner's spiral curriculum principle and quasi-experimental nonequivalent control group design, this study involved 240 students from 6 classes (3 experimental classes, 3 control classes) at a university. The experimental classes received the SCRLM intervention with an alternating pattern of five cycles between case study-based material sessions and flipped classroom project sessions over 13 meetings, while control classes used conventional learning. The results showed that SCRLM obtained a validity score of 94.2% from experts (very valid category). The experimental group demonstrated proposal submission timeliness (90%) and final article submission timeliness (85%) significantly higher than the control group (60% and 50%) with significant Chi-Square tests (p 0.05). The civic disposition of the experimental group increased with an N-Gain of 0.58 (medium category), significantly higher than the control group (N-Gain 0.21) with Independent Sample T-Test showing significant differences (p 0.05). Student responses to SCRLM were very positive (92.1%). This model has proven effective in improving project timeliness and student civic disposition and can be recommended as an innovative learning model for Civics Education in higher education.  Penelitian pengembangan ini bertujuan menghasilkan Spiral Civic Research Learning Model (SCRLM) yang valid dan efektif. Sebuah model Flipped Classroom berbasis Cognitive Apprenticeship dalam Project-Based Learning dengan pendekatan spiral lima siklus untuk meningkatkan ketepatan waktu proyek dan civic disposition mahasiswa pada matakuliah Kewarganegaraan. Menggunakan pendekatan Research and Development dengan model ADDIE yang diintegrasikan prinsip spiral curriculum Bruner dan desain kuasi-eksperimen tipe nonequivalent control group, penelitian ini melibatkan 240 mahasiswa dari 6 kelas (3 kelas eksperimen, 3 kelas kontrol) di salah satu perguruan tinggi. Kelas eksperimen menerima intervensi SCRLM dengan pola selang-seling lima siklus antara sesi materi berbasis studi kasus dan sesi proyek flipped classroom selama 13 pertemuan, sementara kelas kontrol menggunakan pembelajaran konvensional. Hasil penelitian menunjukkan SCRLM memperoleh skor validitas 94,2% dari ahli (kategori sangat valid). Kelompok eksperimen menunjukkan ketepatan waktu pengumpulan proposal (90%) dan artikel final (85%) yang secara signifikan lebih tinggi dibanding kelompok kontrol (60% dan 50%) dengan uji Chi-Square signifikan (p 0,05). Civic disposition kelompok eksperimen meningkat dengan N-Gain 0,58 (kategori sedang) signifikan lebih tinggi dibanding kelompok kontrol (N-Gain 0,21) dengan Independent Sample T-Test menunjukkan perbedaan signifikan (p 0,05). Respons mahasiswa terhadap SCRLM sangat positif (92,1%). Model ini terbukti efektif meningkatkan ketepatan waktu proyek dan civic disposition mahasiswa serta dapat direkomendasikan sebagai inovasi pembelajaran Kewarganegaraan di perguruan tinggi.